Synthesis and photovoltaic performances of benzo[1, 2‐b:4, 5‐b']dithiophene‐alt‐2, 3‐diphenylquinoxaline copolymers pending functional groups in phenyl rings. Issue 5 (4th December 2012) - Tan, Hua; Deng, Xianping; Yu, Junting; Chen, Jianhua; Nie, Kaixuan; Huang, Ying; Liu, Yu; Wang, Yafei; Zhu, Meixiang; Zhu, Weiguo
Abstract Two donor/acceptor (D/A)‐based benzo[1, 2‐b:4, 5‐b′]dithiophene‐alt‐2, 3‐biphenyl quinoxaline copolymers of P1 and P2 were synthesized pending different functional groups (thiophene or triphenylamine) in the 4‐positions of phenyl rings. Their thermal, photophysical, electrochemical, and photovoltaic properties, as well as morphology of their blending films were investigated. The poly(4, 8‐bis((2‐ethyl‐hexyl)oxy)benzo[1, 2‐b:4, 5‐b'] dithiophene)‐alt‐(2, 3‐bis(4′‐bis(N, N‐bis(4‐(octyloxy) phenylamino)‐ 1, 1′‐biphen‐4‐yl)quinoxaline) (P2) exhibited better photovoltaic performance than poly(4, 8‐bis((2‐ethylhexyl)oxy)benzo[1, 2‐b:4, 5‐b'] dithiophene)‐alt‐(2, 3‐bis(4‐(5‐octylthiophen‐2‐yl)phenyl)quinoxaline) (P1) in the bulk‐heterojunction polymer solar cells with a configuration of ITO/PEDOT:PSS/polymers: [6, 6]‐phenyl‐C71‐butyric acid methyl ester (PC71BM)/LiF/Al. A power conversion efficiency of 3.43%, an open‐circuit voltage of 0.80 V, and a short‐circuit current of 9.20 mA cm−2 were achieved in the P2‐based cell under the illumination of AM 1.5, 100 mW cm−2. Importantly, this power conversion efficiency level is 2.29 times higher than that in the P1‐based cell. Our work indicated that incorporating triphenylamine pendant in the D/A‐based polymers can greatly improved the photovoltaic properties for its resulting polymers.